AccessMedicine® Case Files Collection: A Review. Issue 1 (2nd January 2019) - Holloway, Wesley
Abstract: AccessMedicine ® Case Files Collection provides students, residents, faculty, and health care professionals with real patient-physician scenarios from nearly 1, 200 cases in the biomedical sciences and clinical medicine. With a MyAccess profile, users may access their activity and test their knowledge, while faculty may integrate content from the collection into course modules. Each case contains helpful information and activities, including a series of diagnostics questions and full explanations accompanying correct answers; the approach for treatment; anatomy pearls; references; and comprehensive questions on the case. This review describes AccessMedicine ® Case Files Collection based on its coverage, major features, and search functionality.